Socialization of Organic and Inorganic Waste Segregation as a Form of Environmental Concern during the Covid-19 Pandemic in Public Elementary School (SDN)10 Ciamis, Indonesia - Abdul Zamal Sigit (Research Collaboration Community (RCC), 2021)
Community Service is one of the Tri Dharma of Higher Education, especially at Garut University, it is hoped that with this community service the existence of universities can contribute to the development of scientific application to the community. Efforts to protect the surrounding environment must start from oneself by doing small things, educating students about environmental problems due to landfills is needed to raise students' awareness so that they are more concerned with the surrounding environment. Active participation of students can be done in a culture of disposing of waste in its place. However, because of the many categories of waste that exist, it is necessary to educate students about the types of waste, namely; organic, inorganic and B3 waste (hazardous and toxic materials) and their handling.This community service activity method uses the method of delivering socialization material with counseling techniques, questions and answers, quizzes, and by adding games. The results of the research carried out were able to make students leave the old way of just throwing garbage away, but also provide education and familiarize students to sort, select, and categorize waste as well as develop a waste bank so that it has economic value. If this is done, the practice of processing and utilizing waste becomes a real step in managing waste.